Information asymmetries between parents and educators in German childcare institutions - Georg F. Camehl; Pia S. Schober; Christa Katharina Spieß (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Economic theory predicts market failure in the market for early childhood education and care (ECEC) due to information asymmetries. We empirically investigate information asymmetries between parents and ECEC professionals in Germany, making use of a unique extension of the German Socio-Economic Panel Study (SOEP). It allows us to compare quality perceptions by parents and pedagogic staff of 734 ECEC institutions which were attended by children in SOEP households. Parents and staff were asked to rate the same quality measures. We detect considerable information asymmetries between these groups which differ across quality measures but little by parental socio-economic background or center characteristics. Our findings imply that information is not readily available to parents, an issue that should be addressed by policy-makers.
Keywords: J13; D82; I21; 330; child care; quality; information asymmetries; socio-economic differences; Germany